Space mapping-based computational morphogenesis of continuum structures using isolines with free-boundary design domain. (July 2022) - Ma, Zhenfu; Cui, Changyu
Abstract: Computational morphogenesis is widely used in the conceptual design of continuing structures to provide engineers with a desired design. A morphogenetic algorithm of the free-boundary continuum structure using isolines is proposed based on space mapping technology, referred to here as the isolines structural morphogenesis (ISM) method. The free-boundary initial design domain containing a parameter space and physical space is established by B-spline. Mechanics performance is analyzed in arbitrary physical space (the structure itself) and distributed to the regular parameter space. Determine the evolutionary threshold based on the distribution characteristics of design criteria. The threshold's isolines are extracted in the orthogonal grid of the parameter space and mapped to acquire a new structure boundary. A continuum structure with a free boundary that efficiently resists the load is generated by iteratively re-evaluating the behavior and updating the isolines until the required design is achieved. In addition, a coefficient matrix based on a regular grid was introduced to simplify the extraction of the isoline. The introduction of mapping space enriches the original modeling means and optimizes the structural design framework, making the morphogenesis of free-boundary continuum structures simple and efficient. Numerical examples show diverse designs of free-boundary continuum structures that verified the improved approach and revealed a novel design pathway of arbitrarily complex structures.